Proceedings of the 4th International Conference on Research of Educational Administration and Management (ICREAM 2020) 2021
DOI: 10.2991/assehr.k.210212.073
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Organizational Culture on Knowledge Sharing Behavior

Abstract: Knowledge is one of the important sources in an organization. Therefore, knowledge management is needed so that knowledge can be utilized effectively and efficiently. One dimension of knowledge management is knowledge sharing behaviour. This is influenced by many factors. One of them is organizational culture. Unfortunately, the literature that comprehensively reviews the influence of organizational culture on knowledge sharing behaviour has not been widely found. This study aims to fill that gap. This researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 26 publications
(47 reference statements)
1
11
0
Order By: Relevance
“…A conducive organizational culture can enhance a collaborative and innovative culture that enables organizations to adapt to a rapidly changing external environment (Kokt and Makumbe, 2020;McDowell et al, 2016). The influence of organizational culture on IWB can be strengthened by the existence of a mediating variable (Mutonyi, 2021;Sawan et al, 2021) so in this study we propose KS as a mediating variable in CC relationships, with IWB. The assumption is that CC represents a friendly workplace where people share themselves with others in the organization (Bogilovi c et al, 2020), including KS (Sensuse et al, 2021).…”
Section: Clan Culture Knowledge Sharing and Innovative Work Behaviormentioning
confidence: 86%
See 2 more Smart Citations
“…A conducive organizational culture can enhance a collaborative and innovative culture that enables organizations to adapt to a rapidly changing external environment (Kokt and Makumbe, 2020;McDowell et al, 2016). The influence of organizational culture on IWB can be strengthened by the existence of a mediating variable (Mutonyi, 2021;Sawan et al, 2021) so in this study we propose KS as a mediating variable in CC relationships, with IWB. The assumption is that CC represents a friendly workplace where people share themselves with others in the organization (Bogilovi c et al, 2020), including KS (Sensuse et al, 2021).…”
Section: Clan Culture Knowledge Sharing and Innovative Work Behaviormentioning
confidence: 86%
“…These cultural features foster a willingness among organizational members to share their knowledge and experiences (Asurakkody and Kim, 2020). Numerous studies have demonstrated that CC is conducive to KS (Sawan et al , 2021; Sensuse et al , 2021). Engaging in KS activities with colleagues and superiors enhances knowledge dissemination within the organization (Jahidah et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Employees are more dedicated to their work and tasks, participate in achieving strategic goals and formulating and implementing strategy (Sawan, Suryadi & Nurhattati, 2020).…”
Section: Decision Making In Uncertain Situationsmentioning
confidence: 99%
“…Different OCs can elicit different effects of AT in co-workers because of the different tendencies to shape employees' attitudes and behaviors (Schein, 2010). Sawan et al (2021) propose that OC, directly and indirectly, affects knowledge sharing. The level of mutual trust between people is influenced by OC (Jabeen and Isakovic, 2018).…”
Section: Stability and Predictability Internal Focus And Integrationmentioning
confidence: 99%